Literasi Digital Masyarakat Kabupaten Bandung Barat - Takariani, Caecilia Suprapti; Sari, Diana; Pangaribuan, Tristania Risma Anastasia; Simatupang, Oktolina (Jurnal Pekommas, 2023)
Human resources are an important aspect of digital transformation. People's understanding and acceptance of technology, which leads to digital literacy, can drive the success of the digital transformation. An adaptive society is needed to accept existing digital developments, so it is very important to know the data on the digital literacy level of the community in an area to support development in that region. West Bandung Regency (KBB) is one of the areas that carry out digital transformation in various fields of life. This study aims to determine the level of digital literacy in the KBB society, determine the relationship between several sociodemographic factors and digital literacy, and provide recommendations regarding the condition of digital literacy in the KBB society. The research was carried out using a quantitative approach, with a sample of respondents selected by random sampling in the KBB society in seven selected sub-districts. The analysis was carried out both descriptively to determine the level of digital literacy in the KBB society and statistically using the chi-square test to see the relationship between several sociodemographic variables and digital literacy. The results of the study show that the digital literacy level of the people of West Bandung Regency is generally at an intermediate level. There is a relationship between the variables of education level, occupation, and digital literacy in the KBB society.